Socioeconomic and Reproductive Factors Related to Low Birth Weight Babies - Giri, Arun; Sedhain, Raju (Journal of Nobel Medical College, 2016)
Background Birth weight is a major determinant of morbidity, mortality and disability in neonates and children. Low birth weight (LBW) is associated with high morbidity, mortality and lifelong consequences. Hence, it is prudent to identify the risk factors causing LBW neonates and manage them promptly.Material and Methods This study was conducted at Nobel Medical College Teaching Hospital (P.) Ltd.which included term singleton neonates born via normal vaginal route without gross congenital anomalies and sickness at birth. Birth weight of neonate and mother’s socioeconomic and reproductive history was taken within 24 hrs of birth.Results There were 429 infants with birth weight ranging from 1500 gm to 4000 gm with mean birth weight of 2815.84 gm. The incidence of LBW was 21.9% (n=105). Body Mass Index at first Ante Natal Visit (ANV), mother’s age, occupation, smoking, history of abortion and last pregnancy interval were the most important associated variables for LBW.Conclusion Better nutrition during pregnancy, better education of mothers, avoidance of smoking, regular ANV and early commencement of ANV, increasing birth spacing and iron and folic acid supplementation will decrease the incidence of LBW and its consequences.Journal of Nobel Medical CollegeVolume 5, Number 1, Issue 8, January-July 2016, 57-60